2021
DOI: 10.3390/electronics10030361
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy ARTMAP-Based Fast Object Recognition for Robots Using FPGA

Abstract: Fast object recognition and classification is highly important when handling operations with robots. This article shows the design and implementation of an invariant recognition machine vision system to compute a descriptive vector called the Boundary Object Function (BOF) using the FuzzyARTMAP (FAM) Neural Network. The object recognition machine is integrated in the Zybo Z7-20 module that includes reconfigurable FPGA hardware and a RISC processor. Object encoding, description and prediction is carried out rap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The authors in [16] described how BOF elements are extracted. First, these values are stored in a BRAM.…”
Section: Bof Stage Implementationmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors in [16] described how BOF elements are extracted. First, these values are stored in a BRAM.…”
Section: Bof Stage Implementationmentioning
confidence: 99%
“…The boundary object function (BOF) [15] descriptor vector, which is a formalism that characterizes an object by extracting some attributes, as detailed in the following sections, demonstrated potential in terms of being invariant to rotation, scale, and displacement, and being able to condense the information coming from a 2D image to a one-dimensional array. In [16], the BOF and a classifier based on the fuzzy ARTMAP neural network were implemented on an FPGA [17] with very favorable results. However, complications are detected when the object angle on the z-axis exceeds 15 degrees.…”
Section: Introductionmentioning
confidence: 99%
“…Victor et al reported "Fuzzy ARTMAP-Based Fast Object Recognition for Robots Using FPGA" [3]. This article shows the design and implementation of an invariant recognition machine vision system to compute a descriptive vector called the Boundary Object Function (BOF) using the Fuzzy ARTMAP (FAM) Neural Network.…”
Section: The Topics Of Intelligent Electronic Devices and Its Applica...mentioning
confidence: 99%
“…Quantize the contour into n points, where n is the size of the descriptor. With n = 180, the test guarantees a good balance between accuracy and computer performance [13].…”
mentioning
confidence: 99%